Show your beaks and we tell you what you eat: Different ecology in sympatric Antarctic benthic octopods under a climate change context. (September 2019) - Matias, Ricardo S.; Gregory, Susan; Ceia, Filipe R.; Baeta, Alexandra; Seco, José; Rocha, Miguel S.; Fernandes, Emanuel M.; Reis, Rui L.; Silva, Tiago H.; Pereira, Eduarda; Piatkowski, Uwe; Ramos, Jaime A.; et al.
Abstract: Sympatry can lead to higher competition under climate change and other environmental pressures, including in South Georgia, Antarctica, where the two most common octopod species, Adelieledone polymorpha and Pareledone turqueti, occur side by side. Since cephalopods are typically elusive animals, the ecology of both species is poorly known. As beaks of cephalopods are recurrently found in top predator's stomachs, we studied the feeding ecology of both octopods through the evaluation of niche overlapping and specific beak adaptations that both species present. A multidisciplinary approach combining carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope signatures, mercury (Hg) analysis and biomaterials' engineering techniques was applied to investigate the beaks. An isotopic niche overlap of 95.6% was recorded for the juvenile stages of both octopod species, dropping to 19.2% for the adult stages. Both A. polymorpha and P. turqueti inhabit benthic ecosystems around South Georgia throughout their lifecycles (δ 13 C: −19.21 ± 1.87‰, mean ± SD for both species) but explore trophic niches partially different during adult life stages (δ 15 N: 7.01 ± 0.40‰, in A. polymorpha, and 7.84 ± 0.65‰, in P. turqueti ). The beaks of A. polymorpha are less dense and significantly less stiff than in P. turqueti . Beaks showed lower mercury concentration relative to muscle ( A. polymorpha - beaks: 0.052 ± 0.009 μg g −1, muscle: 0.322 ± 0.088 μg g −1 ; P. turqueti - beaks: 0.038 ± 0.009 μg g −1 ; muscle: 0.434 ± 0.128 μg g −1 ). Overall, both octopods exhibit similar habitats but different trophic niches, related to morphology/function of beaks. The high Hg concentrations in both octopods can have negative consequences on their top predators and may increase under the present climate change context.